Tourism Crises and Marketing Recovery Strategies - Scott, Noel; Laws, Eric; Prideaux, Bruce (Journal of travel & tourism marketing, 2008)
The recent frequency and intensity of crises and disasters affecting the tourism industry has resulted in a growing body of research into their causes, effects and management, as the bibliographies of the ensuing papers catalogue. To date, most papers and collections of research have taken a broad approach, describing the origins of a particular event which triggered a tourism crises, followed by an examination of the differential effects of the crisis on local residents, staff, tourists and tourism organizations or the environment and infrastructure. They have also discussed rescue efforts and the complexity of management tasks in the immediate aftermath of an event, often pointing to the need for preplanning to mitigate the consequences of any future disaster. Other researchers have contributed directly to the academic debate about how to theorise tourism crisis management, often by drawing on the wider crisis management literature. The present collection of research differs in that it focuses on one phase of the tasks which managers face after the immediate consequences of a crisis have been dealt with. This phase addresses the question of how to rebuild the market for a tourism service or a destination which has experienced a significant catastrophe, and how to learn from the experience in planning for future crisis response strategies. It is suggested in this paper that the challenges are actually more varied and complex than is implied by the suggestion, found in much of the literature, that the task is about 'restoring normality.' The chaos and complexity experienced in the aftermath of a crisis raise general issues of how organizations learn and adapt to change.